Rectifilter for electric arc plasma plant (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents the results of the development and research of a new type of AC-DC converter - a filter-rectifier (or rectifilter). The object of application of the proposed device is an industrial plant of electric arc plasma processing, the operation of which requires maintaining a constant value of the arc current and is accompanied by a high level of harmonic distortion and consumed reactive energy. From the point of view of the reactive power compensation and harmonic filtering strategy, the rectifilter can be attributed to active electric power filters and FACTS, however, from the position of the main function performed, it is a direct current source, an AC to DC converter, an active rectifier. This work describes in detail the principles of operation of the control system and the hardware architecture of the device. Mathematical modeling of the rectifilter and analysis of the graphs of the consumed alternating current, rectified current, analysis of the harmonic composition and power factor in comparison with the thyristor rectifier of an electric arc plasmatron were carried out.